Generalized equivalent circuit model for ultra wideband antenna structure with double steps for energy scavenging - Heong O.K.; Hock G.C.; Chakrabarty C.K.; Hock G.T. (Institute of Physics Publishing, 2023)
There are various types of UWB antennas can be used to scavenge energy from the air and one of them is the printed disc monopole antenna. One of the new challenges imposed on ultra wideband is the design of a generalized antenna circuit model. It is developed in order to extract the inductance and capacitance values of the UWB antennas. In this research work, the developed circuit model can be used to represent the rectangular printed disc monopole antenna with double steps. The antenna structure is simulated with CST Microwave Studio, while the circuit model is simulated with AWR Microwave Office. In order to ensure the simulation result from the circuit model is accurate, the circuit model is also simulated using Mathlab program. The developed circuit model is found to be able to depict the actual UWB antenna. Energy harvesting from environmental wirelessly is an emerging method, which forms a promising alternative to existing energy scavenging system. The developed UWB can be used to scavenge wideband energy from electromagnetic wave present in the environment. Published under licence by IOP Publishing Ltd.